Nomenclatural notes on the name Asarum longerhizomatosum (Aristolochiaceae) - Deng, Yunfei; Yu, Wenbin (Phytotaxa, 2014)
Asarum longerhizomatosum C.F. Liang & C.S. Yang (Aristolochiaceae) in Liang (1975: 21) was originally described from Guangxi, China. It was widely adopted in Chinese floras (Liang 1991; Cheng & Yang 1988; Yang & Zhou 2000; Huang et al. 2003; Yang & Yang 2006). However, the name was not validly published in 1975 because two gatherings (C.L. Zhang 001 in CMMI and C.L. Zhang 002 in IBK) were designated as types contrary to the requirements of Article 40.1 & 40.2 of International Code of Nomenclature for Algae, Fungi and Plants (McNeil et al. 2012) for the names published on or after 1 January 1958. Huang et al. (2003) presumed the two elements represented duplicates of a single collection and treated the name as validly published. However,searching for type material in herbaria showed that C.L. Zhang 001 and C.L. Zhang 002 were two different gatherings. Three duplicates of C.L. Zhang 002 are found at IBK. Although no duplicate of C.L. Zhang 001 was traced by us, the previous literatures indicated that at least two duplicates exist, one in CMMI (Liang 1975) and another in PTM (Cheng & Yang 1983). It is noted that “PTM” was the acronym of “Beijing Chinese Traditional Medicine College” whose acronym is BCMM now in Index Herbariorum Sinicorum (Fu et al. 1993) and Index Herbariorum (Thiers, [continousely unpdated]).